Knowledge, attitude, and practice of menstrual blood-derived mesenchymal stem cells among female healthcare workers in India - Kaur, Karuna Nidhi; Nandi, Dhruva; Ramachandran, Krithika; Mohanan, Lita; Subhashini, S.; Segan, Mehak; Tripathy, Saswaty; Janardhanan, Rajiv (Frontiers in Public Health, 2023)
Introduction Mesenchymal stem cells (MSCs) are pluripotent progenitor cells that can be differentiated into a variety of specialised cell types. Menstrual blood, like umbilical cord blood and bone marrow stem cells, is a rich source of MSCs with proliferative properties. This research was conducted to understand the knowledge, attitude as well as practice of menstrual blood donation for culturing menstrual blood derived mesenchymal stem cells (MenSCs) among female healthcare workers in India. Methodology A cross-sectional online and offline survey was conducted at the national level between November 20th, 2021, and March 10th, 2022. A self-constructed semi-structured questionnaire was distributed through google forms on various social media platforms. The questionnaire was self-administered, and data was collected using purposive sampling technique. Results A total of 499 respondents completed the questionnaire. Forty-nine percent of the respondents had adequate knowledge, fifty-four percent showed positive attitude and forty-five percent reported adequate practices regarding menstrual blood donation and the usage of related products. Educational background, occupational status as well as monthly income of the participants were found to be significantly associated with their attitude towards MenSCs. Conclusion There is a need to promote interactive sessions on MenSCs among health care professionals in order to bridge the gap between general populations and the healthcare setting. Enhancing knowledge and awareness regarding the potential benefits of MenSCs would help in dissipating the age-old myths associated with menstruation and will benefit the society as a whole. Keywords: - Mesenchymal stem cells (MSCs), Menstrual Blood-Derived Mesenchymal Stem Cells (MenSCs), Health Care workers, India